FCSIT GRANT MANAGEMENT SYSTEM - Chye, Kim Quan (Universiti Malaysia Sarawak (UNIMAS), 2022)
Nowadays, the management of the grant application is still lack of a platform in the Faculty of Computer Science and Information Technology, Universiti Malaysia Sarawak. Currently, the grant management is worked using the UNIMAS Morpheus system but the UNIMAS Morpheus system has the weakness which does not provide the infrastructure to support the grant management sucy as provide the comment on the grant proposal. Hence, this project is to deliver a solution for the problem statement which is implementing a Grant Management System to help the administrator and other users to manage the grant application